Animal food products: policy, market and social issues and their influence on demand and supply of meat. Issue 2 (5th May 2021) - Henchion, Maeve; Zimmermann, Jesko
Abstract : The present paper aims to contribute to the contentious debate regarding the role of meat as part of a sustainable diet. It uses secondary data to examine the patterns of meat consumption across the globe, and drawing on academic and grey literature, it outlines some of the policy, market and social trends and issues influencing demand and supply of meat. It also presents an overview of the scientific evidence base regarding the pros and cons of meat consumption. The results show that consumption patterns are not homogeneous globally, nor across meat types, with overall meat consumption increasing strongly in developing countries but stagnating in developed countries, and demand for poultry increasing in most regions in contrast to beef. They also illustrate the evolving impact of factors such as income on consumption and the increasing impact of non-economic factors, such as social and policy influences relating to health and the environment, on food choice behaviours, to the extent that such behaviours are increasingly entering a moral space. Given the solid scientific evidence that simultaneously substantiates arguments to increase and decrease meat consumption, it is clear that dietary recommendations need to be context-specific. An important part of the context is the strategies being pursued by researchers and supply chain actors, from farmers through to processors, retailers and food service operators, to improve the sustainability credentials of livestock production. As new evidence emerges from such initiatives, the context will change which means that dietary guidelines will require continuous review.